5th-grade Students' Misunderstandings and Misconceptions about Fungi - Gul, Seyda (Mimbar Sekolah Dasar, 2021)
The fungi kingdom is among the important topics of biology, and students can develop misunderstandings and misconceptions about this subject.This study aims to determinemisunderstandings and misconceptions of 5th-grade students about fungi. The participants of the study consisted of 22 (12 girls, 10 boys) fifth graders of an elementary school in Erzurum city center, which was determined by the convenience sampling method. In this qualitative study, a 'semi-structured interview form' was used. The form includes 16 open-ended questions prepared following the learning outcomes of the curriculum. The data collected in the study were subjected to descriptive analysis and the findings were presented by calculating the frequency and % values. The findings indicate that the students have misunderstandings and misconceptions on the structure of mold, yeast, and fungi, their feeding, whether they are alive, their classification, reproduction, living conditions, etc.At the end of the study, some suggestions were made on the teaching of the biology concepts with examples from daily life, usage of visual elements during teaching, more laboratory applications. It is also suggested that similar studies should be implemented with different grade levels and sample groups.